Biotransformation of labdane and halimane diterpenoids by two filamentous fungi strains - Monteiro, Afif F. [UNESP]; Seidl, Claudia; Severino, Vanessa G. P.; Cardoso, Carmen Lucia; Castro-Gamboa, Ian [UNESP] (The Royal Society, 2017)
Biotransformation of natural products by filamentous fungi is a powerful and effective approach to achieve derivatives with valuable new chemical and biological properties. Although diterpenoid substrates usually exhibit good susceptibility towards fungi enzymes, there have been no studies concerning the microbiological transformation of halimane-type diterpenoids up to now. In this work, we investigated the capability of Fusarium oxysporum (a fungus isolated from the rhizosphere of Senna spectabilis) and Myrothecium verrucaria (an endophyte) to transform halimane (1) and labdane (2) acids isolated from Hymenaea stigonocarpa (Fabaceae). Feeding experiments resulted in the production of six derivatives, including hydroxy, oxo, formyl and carboxy analogues. Incubation of 1 with F. oxysporum afforded 2- oxo-derivative (3), while bioconversion with M. verrucaria provided 18,19-dihydroxy (4), 18-formyl (5) and 18-carboxy (6) bioproducts. Transformation of substrate 2 mediated by F. oxysporum produced a 7α-hydroxy (7) derivative, while M. verrucaria yielded 7α- (7) and 3β-hydroxy (8) metabolites. Unlike F. oxysporum, which showed a preference to transform ring B, M. verrucaria exhibited the ability to hydroxylate both rings A and B from substrate 2. Additionally, compounds 1–8 were evaluated for inhibitory activity against Hr-AChE and Hu-BChE enzymes through ICER-IT-MS/MS assay.
Keywords: Anticholinesterase inhibitors; Fusarium oxysporum; Labdane and halimane diterpenoids; Myrothecium verrucaria; Whole-cell biotransformation